2005
DOI: 10.1007/s11282-005-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of viewing conditions on the detection of contrast details on intraoral radiographs

Abstract: Objectives. To quantify the effects of changes in the viewing environment on the detectability of diagnostic information on intraoral radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
1
0
1
Order By: Relevance
“…The researchers found that the detectability of structures on high‐density films was maximized when using a darkened room and the use of a viewing box with masking. For low‐density radiographs, Kawai et al. (2005) found that the identification of structures was compromised for all three viewing conditions confirming the findings of Welander et al.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The researchers found that the detectability of structures on high‐density films was maximized when using a darkened room and the use of a viewing box with masking. For low‐density radiographs, Kawai et al. (2005) found that the identification of structures was compromised for all three viewing conditions confirming the findings of Welander et al.…”
Section: Discussionsupporting
confidence: 65%
“…However, for low‐density films, Espelid (1987) reported that normal room illumination gave the most appropriate environment, whilst Arnold (1987) recommended examining the low‐density film using daylight from a window. A more recent study by Kawai et al. (2005) examined a number of films with a wide range of optical densities using three different viewing conditions: a lighted room without viewing box masking, a lighted room with viewing box masking and finally a darkened room with viewing box masking.…”
Section: Discussionmentioning
confidence: 99%
“…Begitu pula jarak antara interpretator dengan illuminator juga turut berpengaruh (Thrall & Widner 2013). Kondisi ruangan dan jarak yang bervariasi dapat menyebabkan ketidaksepahaman dalam proses interpretasi sebagai akibat dari respon sel kerucut dan batang pada mata pada kondisi gelap dan terang yang berbeda antar individu (Kawai et al 2005). Nilai opasitas berupa derajat hitam, abu dan putih dapat menjadi petunjuk adanya kelainan pada objek yang berguna dalam proses penegakan diagnosa (Thrall & Widner 2013).…”
Section: ■ Pendahuluanunclassified